Achieving Economic Benefits Through Agricultural Trade Reforms in Indonesia - Dermoredjo, Saktyanu Kristyantoadi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2008)
The Indonesian economy has achieved a remarkable transformation from an agricultural economy to a modern economy that is estimated to grow at a high rate of 6 per cent. Sustaining it requires the continual adoption of economic reforms. Part of it requires the adoption of freer trade practices in sectors of the economy where resources are retained due to large government assistance. This paper aims to examine the economy-wide effects of a bilateral agricultural trade liberalization program between Australia and Indonesia. The analytical framework adopted in this paper is a global general equilibrium model known as GTAP (Global Trade Analysis Project). Increasing the agricultural trade between Australia and Indonesia will lead to benefits arising from higher incomes and resource allocation efficiency. In this study, the removal of tariffs on agricultural imports in Indonesia resulted in efficiency gains of US 1.67 – 3.35 million and GDP increase by US 3.55 – 7.08 million. This shows that freer trade practices contribute to the economic growth process in Indonesia.